2018
DOI: 10.14419/ijet.v7i3.21.17224
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Among Language Learning Strategy, Motivation, Anxiety and Autonomy in Chinese EFL Learners

Abstract: This study attempted to explore the relationships among language learning strategy, motivation, anxiety and learner autonomy. Cluster sampling method was adopted to select 600 non-English major students as subjects at three universities in Henan province, China. Quantitative data collected from questionnaires was analyzed by SPSS 19.0. Results from Pearson correlation analysis showed that among the three investigated variables, language learning strategy and motivation had a significant positive relationship w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 3 publications
8
22
0
Order By: Relevance
“…Studies on learner autonomy have also attempted to find the interaction between LA and motivation (Bacquet, 2017;Gardner & Yung, 2015;Ma & Ma, 2012), LA and gender (Kırmızı & Kıraç, 2018;Koçak, 2003;Razeq, 2014), and LA and language proficiency (Jianfeng et al, 2018;Karatas et al, 2015;Mohamadpour, 2013). To extend the research on and gain further insights into the factors affecting LA, this study investigated the role of gender and major of study on students' perceptions of their readiness for autonomy.…”
Section: Research On Students' Readiness For La In Non-western Contextsmentioning
confidence: 99%
“…Studies on learner autonomy have also attempted to find the interaction between LA and motivation (Bacquet, 2017;Gardner & Yung, 2015;Ma & Ma, 2012), LA and gender (Kırmızı & Kıraç, 2018;Koçak, 2003;Razeq, 2014), and LA and language proficiency (Jianfeng et al, 2018;Karatas et al, 2015;Mohamadpour, 2013). To extend the research on and gain further insights into the factors affecting LA, this study investigated the role of gender and major of study on students' perceptions of their readiness for autonomy.…”
Section: Research On Students' Readiness For La In Non-western Contextsmentioning
confidence: 99%
“…It seems that very few studies focused on Englishmajor students' LA performance in comparison to students of different majors. For example, Chen and Li (2014) and Jianfeng, Raj and Ai (2018) investigated the LA of English-major students in light of other factors, which are beyond the scope of the study. Although the current study found a slightly significant difference between the two groups, this difference was more toward the non-English-major students.…”
Section: Discussionmentioning
confidence: 99%
“…It found the participants' professional knowledge, language ability, and research ability are the main influencing factors in their autonomy. In another study by Jianfeng, Raj, and Ai (2018), English-major participants' LA was investigated in correlation with language proficiency. The study found that participants' LA significantly correlated with their language proficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A vast number of scholars and practitioners in the fields of English language teaching have investigated the topics of learner autonomy and motivation during the past few decades. The correlation between motivation, autonomy and English proficiency has been sufficiently explored in China with the participation of 458 non-English major students from one university in Henan province [31], and 229 Englishmajored final-year students at a university in Vietnam [32]. The relationship between autonomy and English proficiency has been examined in different universities in Indonesia through Melvina and Julia's study [33] with 40 second-year undergraduate English majors and Myartawan et al's research [34] with 120 first-semester English-majored students.…”
Section: Research On Relationship Between Autonomy Motivation and Eng...mentioning
confidence: 99%
“…To answer two RQs, the study adopted a quantitative approach, widely recognised as systematic, controlled and objective [39] and useful for the description and/or explanation of numerical relationships [40] Particularly, the correlational relationship method was used to collect data on two variables to examine a relationship between them [41]. This research methodology is in line with numerous previous studies conducted by Jianfeng et al, [31], Khoiriyah [35], Melvina & Julia [33], Phuong and Vo [32], and Syafrizal et al, [37] The study was conducted in the Foreign Language Department at Vinh University, Vietnam. The main participants were 200 first-year English majors who have taken the General English module in the second semester in 2020.…”
Section: Research Design and Participantsmentioning
confidence: 99%